2021
DOI: 10.1016/j.abrep.2021.100387
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of addictive behaviours among adolescents from 73 low-and middle-income countries

Abstract: Highlights The prevalence of regular alcohol use was the highest among adolescents in Zambia but the lowest in Senegal. The prevalence of problematic alcohol use was higher in Argentina and Colombia than in any other low- and middle-income countries. The prevalence of regular and problematic alcohol use was the lowest in countries with Muslim and Buddhist religions. Samoa had the highest prevalence of smoking as well as in marijuana and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 24 publications
1
18
1
Order By: Relevance
“…There were no significant changes in the frequency of opiate or cocaine use, possibly because the number of clients using opiates or cocaine was quite low. This reflects Zambian reports showing substances most frequently used by homeless youth were alcohol, inhalants, and marijuana ( de la Torre-Luque et al, 2021 , Lemba, 2002 , Tyler et al, 2016 ), while cocaine and opiates were more expensive and less available. Clients significantly increased in motivation to change and participation/open-sharing, with large effect sizes, while substance use decreased.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…There were no significant changes in the frequency of opiate or cocaine use, possibly because the number of clients using opiates or cocaine was quite low. This reflects Zambian reports showing substances most frequently used by homeless youth were alcohol, inhalants, and marijuana ( de la Torre-Luque et al, 2021 , Lemba, 2002 , Tyler et al, 2016 ), while cocaine and opiates were more expensive and less available. Clients significantly increased in motivation to change and participation/open-sharing, with large effect sizes, while substance use decreased.…”
Section: Discussionsupporting
confidence: 56%
“…Zambia is one of the African nations with the greatest alcohol consumption ( WHO, 2015 ) and greatest prevalence of regular alcohol use in adolescents compared to 73 other low and middle-income countries ( de la Torre-Luque et al, 2021 ). Other substances abused in Zambia include marijuana, cigarettes, opiates, cocaine, and inhalants such as glues and petrol.…”
Section: Introductionmentioning
confidence: 99%
“…Psychoactive substance use among adolescents is an international health concern [ 1 , 2 ]. For most youth, experimenting with psychoactive substances, such as using cannabis, stimulants, or hallucinogens, is a transient behavior and diminishes as they mature.…”
Section: Introductionmentioning
confidence: 99%
“…The World Health Organization"s 2014 report found that the prevalence of alcohol use disorders among male and female populations aged 15 years in Zambia was 7.9% and 1.0% giving a higher overall rate of 4.5% above the average of 3.3% for the World Health Organization African Region 4 . To crown it all, a study designed to assess prevalence of addictive behaviours among young people from 73 low and middle income countries by de la Torre-Luque et al, ( 2021) found that the prevalence of regular alcohol use was the highest in Zambia and lowest in Senegal 6 . During the commemoration of the 2022 International Day Against Drug Abuse and Illicit Trafficking, the Drug Enforcement Commission"s report of 810 clients managed in 2021 7 , the nation was made to understand the extent of the problem.…”
Section: Introductionmentioning
confidence: 99%